Information construction in centers for disease control and prevention: a nationwide online survey at provincial level and in pilot regions - Shaoqiong LI; Jiaqi MA; Meng CHEN; Xue-jie DU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the status quo of information construction in centers for disease control and prevention (CDCs) of provincial level and in pilot regions across China. Methods An online questionnaire survey was conducted among 32 provincial-level CDCs and 31 prefecture-level and 29 county/district level CDCs in pilot regions during 2021 via China Disease Prevention and Control Information System. ResultsFor the CDCs surveyed, there were totally 341 full-time staff engaged in the information construction. Of all the CDCs, 56.04% established specific information departments; 62.64% had the information construction fund less than 1% of their total expenditure; 43.96% put the information construction into the scope of performance evaluation; and 72.83% paid special attention to the integration of new technologies and the information construction. During 2019 - 2021, the professionals of the investigated CDCs were involved in the formulation or revision of 16 standards on health information and the publication of 187 papers about informatization. The Immunization Program Information System was operated in all the provincial CDCs surveyed, together with infectious disease surveillance and early warning system and mental health management system established in 50% and 59.38% of the provincial CDCs. Cross-sectoral information sharing was carried out in 12 provincial CDCs and 3 prefecture-level CDCs in pilot regions. ConclusionThe pilot work of information construction for disease control has promoted the improvement of the national information system for disease control. However, there are still some problems such as lack of investment, regional imbalance, insufficient specific informatizition support, connectivity and management collaboration.